1998
DOI: 10.1104/pp.118.3.885
|View full text |Cite
|
Sign up to set email alerts
|

Fucosyltransferase and the Biosynthesis of Storage and Structural Xyloglucan in Developing Nasturtium Fruits

Abstract: Young, developing fruits of nasturtium (Tropaeolum majus L.) accumulate large deposits of nonfucosylated xyloglucan (XG) in periplasmic spaces of cotyledon cells. This "storage" XG can be fucosylated by a nasturtium transferase in vitro, but this does not happen in vivo, even as a transitory signal for secretion. The only XG that is clearly fucosylated in these fruits is the structural fraction (approximately 1% total) that is bound to cellulose in growing primary walls. The two fucosylated subunits that are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Separate tests showed that the labelled TCA-soluble product in this experiment was not depolymerized by Pronase, but was digested by cellulase to fragments that fractionated on columns of Bio-Gel P2 to positions equivalent to XG subunits. HPLC of these fragments through Dionex columns indicated that "%C was confined to the same two oligosaccharides observed in TCAsoluble products formed from UDP-["%C]Gal by pea enzyme [12], which are different from the subunits found in storage XG [8]. We are obliged to conclude that present tests with nasturtium vesicles only recovered galactosyltransferase activity that was responsible for biosynthesis of structural (wall) XG, not the great bulk of reserve XG.…”
Section: Table 3 Effects Of Anti-rgp On Galactosyl Transfer From Udp-mentioning
confidence: 72%
See 3 more Smart Citations
“…Separate tests showed that the labelled TCA-soluble product in this experiment was not depolymerized by Pronase, but was digested by cellulase to fragments that fractionated on columns of Bio-Gel P2 to positions equivalent to XG subunits. HPLC of these fragments through Dionex columns indicated that "%C was confined to the same two oligosaccharides observed in TCAsoluble products formed from UDP-["%C]Gal by pea enzyme [12], which are different from the subunits found in storage XG [8]. We are obliged to conclude that present tests with nasturtium vesicles only recovered galactosyltransferase activity that was responsible for biosynthesis of structural (wall) XG, not the great bulk of reserve XG.…”
Section: Table 3 Effects Of Anti-rgp On Galactosyl Transfer From Udp-mentioning
confidence: 72%
“…Nasturtium fruits or excised cotyledons were harvested at 23 days post-anthesis, when they were about half developed and actively synthesizing reserves like XG [8]. Tissues were homogenized with a high-speed blender in a standard extraction medium [12].…”
Section: Enzyme Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Pea cell wall XG is thought to be constituted almost completely of alternating -XXXG-(Glc 4 Xyl 3 ) and -XXFG-subunits (4), but recent study (5) has also detected the presence of small amounts of other subunits including two octasaccharides and the decasaccharide -XLFG-(Glc 4 Xyl 3 Gal 2 Fuc). This subunit (-XLFG-) has also been detected in sycamore cell XG (6), Arabidopsis and rapeseed (7), apple fruit (8), and developing nasturtium fruits (9). An unadecasaccharide, -XFFG-(Glc 4 Xyl 3 Gal 2 Fuc 2 ), has additionally been observed in sycamore cell XG (6).…”
mentioning
confidence: 97%